Kajian Perubahan Sifat Fisika Tanah Inceptisol Melalui Pemberian Bahan Organik Dari Limbah Kulit Pisang - Andi, Darmin La; Sofyan, Adnan; Hartati, Tri Mulya; Hasan, Asrul Dedy Ali (Jurnal Pertanian Khairun, 2023)
Banana peel waste is a source of environmental pollution because it will rot and cause an unpleasant odor and disrupt the cleanliness of the surrounding environment if it is not processed immediately. Therefore, the use of organic fertilizer from banana peel waste is an important step to overcome this problem. This research was conducted in Tabona Village, South Ternate. The method used in this research was a randomized block design (RAK) consisting of 5 treatments, namely (P0) without control, (P1) banana peel waste 10 tons/ha), (P2) banana peel waste 20 tons/ha), (P3) banana peel waste 30 tonnes/ha and (P4) banana peel waste 40 tonnes/ha. Each treatment was repeated 4 times so that the number of experimental units was 5x4 = 20 experimental units. The results of the research show that the application of organic fertilizer from banana peel waste can provide changes in several physical properties of inceptisol soil, namely soil volume weight, soil porosity, soil organic C, % soil water content and soil permeability, stability of soil aggregates.Abstract. Banana peel waste, porosity, C-organic, % water content, permeability, soil aggregate stability